Ventricular tachycardia ablation through radiation therapy (VT-ART) consortium: Concept description of an observational multicentric trial via matched pair analysis - Cellini, Francesco; Narducci, Maria Lucia; Pavone, Chiara; Bencardino, Gianluigi; Perna, Francesco; Pinnacchio, Gaetano; Chiesa, Silvia; Massaccesi, Mariangela; Gambacorta, Maria Antonietta; Manfrida, Stefania; Longo, Silvia; Mannocci, Alice; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Monomorphic ventricular tachycardia (VT) is a life-threatening condition often observed in patients with structural heart disease. Ventricular tachycardia ablation through radiation therapy (VT-ART) for sustained monomorphic ventricular tachycardia seems promising, effective, and safe. VT-ART delivers focused, high-dose radiation, usually in a single fraction of 25 Gy, allowing ablation of VT by inducing myocardial scars. The procedure is fully non-invasive; therefore, it can be easily performed in patients with contraindications to invasive ablation procedures. Definitive data are lacking, and no direct comparison with standard procedures is available. Discussion The aim of this multicenter observational study is to evaluate the efficacy and safety of VT-ART, comparing the clinical outcome of patients undergone to VT-ART to patients not having received such a procedure. The two groups will not be collected by direct, prospective accrual to avoid randomization among the innovative and traditional arm: A retrospective selection through matched pair analysis will collect patients presenting features similar to the ones undergone VT-ART within the consortium (in each center independently). Our trial will enroll patients with optimized medical therapy in whom endocardial and/or epicardial radiofrequency ablation (RFA), the gold standard for VT ablation, is either unfeasible or fails to control VT recurrence. Our primary outcome is investigating the difference in overall cardiovascular survival among the group undergoing VT-ART and the one not exposed to the innovative procedure. The secondary outcome is evaluating the difference in ventricular event-free survival after the last procedure (i.e., last RFA vs. VT-ART) between the two groups. An additional secondary aim is to evaluate the reduction in the number of VT episodes comparing the 3 months before the procedure to the ones recorded at 6 months (from the 4th to 6th month) following VT-ART and RFA, respectively. Other secondary objectives include identifying the benefits of VT-ART on cardiac function, as evaluated through an electrocardiogram, echocardiographic, biochemical variables, and on patient quality of life. We calculated the sample size (in a 2:1 ratio) upon enrolling 149 patients: 100 in the non-exposed control group and 49 in the VT-ART group. Progressively, on a multicentric basis supervised by the promoting center in the VT-ART consortium, for each VT-ART patient enrollment, a matched pair patient profile according to the predefined features will be shared with the consortium to enroll a patient that has not undergone VT-ART. Conclusion Our trial will provide insight into the efficacy and safety of VT-ART through a matched pair analysis, via an observational, multicentric study of two groups of patients with or without VT-ART in the multicentric consortium (with subgroup stratification into dynamic cohorts).